If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + -1x = 10 Solving 85 + -1x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-85' to each side of the equation. 85 + -85 + -1x = 10 + -85 Combine like terms: 85 + -85 = 0 0 + -1x = 10 + -85 -1x = 10 + -85 Combine like terms: 10 + -85 = -75 -1x = -75 Divide each side by '-1'. x = 75 Simplifying x = 75
| 23-(7t-7)=45t-4 | | 5(2x-1)+2=7(x+3) | | J-647=353 | | -3x+6-2x=7x+8 | | -36+s=31 | | -396=-9(8x-12) | | 6(2x-4)=3(4x-22) | | 4a+3=-9 | | p^2-10p-15=0 | | 3t-18=4t-16 | | 6x-2=70 | | -498=6(9x+16) | | 20=-3x+7(-2x+25) | | -7(x+8)-44=3-61 | | 8x^3-336x^2+2760x+1608= | | 2(7-3x)+1=2x-1 | | (3x+4)(x-3)=10 | | 8+-176=-72 | | 567=-6(10x-16) | | 8+176=-72 | | (x-8)*(x-8)-18=-2 | | 4k-7=2+k | | 504=-16x^2+484 | | 2(g-2)-4=3(g-3) | | 209-3x=33x+21 | | 75-6x=12x+15 | | 3+5d=11+4d | | 6x-7=3x-11 | | 9(2x+14)-4(3x+17)=64 | | -3x+6=18 | | 3x^2-27x=-2x^2-9x-16 | | 5.50+4.00(486-a)=2416 |